Leigh's disease: significance of the biochemical changes in brain. Issue 11 (November 1975) - Murphy, J V; Craig, L
Abstract : Analysis of five brains from patients with Leigh's disease demonstrates an accumulation of thiamine pyrophosphate and a deficiency of thiamine triphosphate. The enzyme which converts thiamine pyrophosphate to thiamine triphosphate was normally active in two of these brains, suggesting that the inhibitor found in Leigh's disease is probably producing the observed neurochemical changes. Reasons for the histological similarity between Leigh's and Wernicke's diseases are suggested.